Flock-level seroprevalence against avian pneumovirus amongst uruguayan broiler chickens - Giossa, G. (2011)
The objective of this study was to estimate the true prevalence of seropositive broiler chickens against avian pneumovirus at flock-level in Uruguay, using the Rogan-Gladen estimator in conjunction with Bayesian inference. A total of 181 pooled samples (consisting of 10 individual-chicken sera each) from the study area were examined with the enzyme-linked immunosorbent assay. All individual-chicken samples in the pools were also examined with the same assay. Forty-four pools were classified as test positive, because they included at least one individual-chicken classified as positive. The estimates for the deterministic (Rogan-Gladen approach) and stochastic (Bayesian approach) true prevalence were 30.9% [95% confidence interval (CI): 26.8-35.0%] and 31.4% (95% CI: 15.4-49.5%), respectively.